A mitochondria-targeted fluorescent probe for imaging endogenous malondialdehyde in HeLa cells and onion tissues. Issue 29 (28th March 2017) - He, Longwei; Yang, Xueling; Xu, Kaixin; Lin, Weiying
Abstract : A turn-on mitochondria-targeted fluorescent probe (Mito-FMP ) was engineered for monitoring endogenous malondialdehyde in HeLa cells and onion tissues. Abstract : The mitochondria-targeted turn-on fluorescent probe (Mito-FMP ) based on a benzoxadiazole platform was developed for detection of malondialdehyde (MDA).Mito-FMP performed with large enhancement of the optical signal (774-fold) in response to MDA in an aqueous system and has the capability of monitoring endogenous MDA in HeLa cells and onion tissues.